PROBLEMS IN THE FORMATION OF COMMON EUSOCIAL POLICY - Rutkauskienė, Lina (Ekonomika, 2009)
European Union social policy is a popular subject of research in the academic circles and is an important topic for its every member state and its citizens. The formation of a common social policy in the EU has an interesting history and related issues, thus this article is an attempt to find out why certain difficulties are encountered in the integration of social affairs, and to offer certain l suggestions for their l improvement. The aim of this study is to reveal the problems encountered in the formation of common EU social policy in the context of its development. The article presents some analysis of the history of the development of the European Community to determine the position of the goal to have a common social policy in the integration processes and the attention is given to the examination of the variety of social policy models in the EU member states as one of the problems of the integration of social policy. Furthermore, using an analysis of the academic literature, this article evaluates the main social policy management-coordination measure – the Open Method of Coordination, and presents the arguments highlighting its inefficiency , comments on its structure and organisation, and suggests the ways of improving this method.p>